XPS and optical studies of different morphologies of ZnO nanostructures prepared by microwave methods - Rashad, Al-Gaashani; Shahidan, Radiman, Prof. Dr.; Abdul Razak, Daud, Prof. Dr.; Nouar, Tabet, Prof. Dr.; Yarub, Al-Douri, Assoc. Prof. Dr. (Elsevier, 2013)
Link to publisher's homepage at www.elsevier.com